A New Frontier: Improving Nursing Care for People With Dementia and Delirium in Hospitals. (December 2015) - Graham, Frederick
Abstract : Frederick Graham, a clinical nurse consultant from Princess Alexandra Hospital in Brisbane, Australia, presents this month's column focused on improving nursing care for people with dementia and delirium in hospitals.